Dry matter production and nutritive value of forage of Digitaria eriantha cv. Irene in two locations oft be central semi-arid region of Argentina (Semiárida, 2020)
The aim of this experiment was to compare dry matter (DM) production rates and nutritive value of a warm-season grass, Digitaria erisntha ev. Irene, in two locations of Central Argentina, Santa Rosa (SR) and Villa Mercedes (VM). The plants were established in two identical groups of plots, within a randomized block design DM rates were calculated from serial, out of phase clippings, and in vitro dry matter digestibility (IVDMD) and crude protein (CP) content analyzed on subsamples. The study lasted for three consecutive growing seasons. Results showed that DM production rates were generally higher (P